A Study on In Vitro Interaction of Cephradine with Mango Juice at Lower pH - Mallik, Jony (International Journal of Pharmaceutical & Biological Archive, 2012)
A Study on In Vitro Interaction of Cephradine with Mango Juice at Lower pH